1996
DOI: 10.1161/01.str.27.10.1874
|View full text |Cite
|
Sign up to set email alerts
|

Global Ischemia Impairs ATP-Sensitive K + Channel Function in Cerebral Arterioles in Piglets

Abstract: Ischemia transiently eliminates cerebral arteriolar dilation to activation of ATP-sensitive K+ channels; arteriolar responses are suppressed at 1 hour and return toward normal over 2 to 4 hours. In addition, reduced responsiveness can be prevented by prior treatment with indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 24 publications
3
60
1
Order By: Relevance
“…Indomethacin has been suggested to inhibit prostacyclin receptors (33), and a 'double-blockade' effect both at the enzyme and receptor level may explain the conspicuous efficacy of indomethacin. Unfortunately, others found iloprost-induced vasodilation intact after indomethacin (8). Conceivably, indomethacin may interfere quite specifically with the yet unknown, enigmatic mechanism of hypercapnia-induced vasodilation.…”
Section: Cox-dependent Vascular Responses In Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indomethacin has been suggested to inhibit prostacyclin receptors (33), and a 'double-blockade' effect both at the enzyme and receptor level may explain the conspicuous efficacy of indomethacin. Unfortunately, others found iloprost-induced vasodilation intact after indomethacin (8). Conceivably, indomethacin may interfere quite specifically with the yet unknown, enigmatic mechanism of hypercapnia-induced vasodilation.…”
Section: Cox-dependent Vascular Responses In Pigsmentioning
confidence: 99%
“…However, COX inhibitors may also indirectly produce neuroprotection by preserving the ischemia-sensitive elements of cerebrovascular reactivity. Indeed, indomethacin prevented the postischemic attenuation of cerebrovascular reactivity to numerous stimuli that dilated pial arterioles through COX-independent pathways (7,8). However, a number of ischemia-sensitive vasodilatory mechanisms are themselves COX-dependent, thus COXinhibitors given for neuroprotection should simultaneously impair cerebrovascular control to some extent.…”
mentioning
confidence: 99%
“…Thus, indomethacin pretreatment preserves arteriolar dilator responses to CGRP, apri kalim, and iloprost after ischemia . 43,44 There are at least three striking parallels between behavior of glutaminergic receptors and K channels with respect to cerebrovascular control mechanisms following ischemic stress . First, effects of ischemia are usually transient.…”
Section: Cerebrovascular Receptors and Ion Channelsmentioning
confidence: 99%
“…In our laboratory, the newborn piglet model has long been used to study the morphology and functional responses of cerebrovascular system in physiologic and pathologic conditions [61][62][63][64][65][66][67]. We and others have repeatedly shown that hypoxic-ischemic stress in newborn piglets severely attenuated CR to various so called "hypoxia-ischemia sensitive" stimuli determined in pial arterioles 1 hour after the insult [61,64,[68][69][70].…”
Section: Animal Models In Hie Researchmentioning
confidence: 99%
“…Blood pressure, tissue oxygenation and body temperature were not monitored and potential derangements in these parameters over the course of the 24h survival period could occur and contribute to the observed attenuation of CR. Furthermore, confounding data emanated from a more recent set of studies, in which the attenuated CR to numerous stimuli (hypercapnia, NMDA, the ATP-sensitive potassium channel agonist aprikalim, and the prostacyclin analogue iloprost) spontaneously recovered 2-4 hours after hypoxic/ischemic stress [62,63,68]. In these studies, global cerebral ischemia was also performed with the same technique, however, in anesthetized animals and the duration of the anoxic stress was only 10 min.…”
Section: Map-2 Densitymentioning
confidence: 99%